Uma abordagem sobre a segurança da informação no mundo atual - MENDES, Joyce de Andrade (2022)
In the last decade, technology has become an essential part of the day-to-day life of organizations and is increasingly present in people's lives, it is currently one of the main means of communication. In this way, the amount of data processed or stored is immeasurable, ranging from simple text messages to bank details and, for organizations, their data represents one of the most valuable assets, being fundamental for business continuity. Thus, information security becomes essential, not only in the business sphere, but also for society. In this course conclusion work, the topic of information security, concept, purpose, principles, vulnerabilities and its role in today's world.